AUTONOMY SUPPORT IN STRENGTH AND CONDITIONING - Jeffrey C. Pagaduan; Matt Kritz; Philip M. Wilson; António Labisa da Silva Palmeira (Sport Scientific And Practical Aspects, 2025)
Previous research and commentary has underscored the importance of providing support for autonomy and promote physical and psychological well-being amongst exercisers and athletes. Autonomy support concerns the degree to which actions perceived to emanate from significant others which are supportive of individual choices, recognize the difficulty of behavioral change, and engage with others in an empathic manner. In the sport-training context, the coach plays an important role in nurturing the need for autonomy, the need for relatedness and the need for competence to facilitate self-determined motivational orientation. The overall aim of this article is to discuss the implications of providing autonomy support for individuals engaged in strength and conditioning activities.